Effect of Intra-Articular Hyaluronic Injection on Postural Stability and Risk of Fall in Patients with Bilateral Knee Osteoarthritis - Nafiseh Khalaj; Noor Azuan Abu Osman; Abdul Halim Mokhtar; John George; Wan Abu Bakar Wan Abas (The Scientific World Journal)
Knee osteoarthritis is a common cause of disability which influences the quality of life. It is associated with impaired knee joint proprioception, which affects postural stability. Postural stability is critical for mobility and physical activities. Different types of treatment including nonsurgical and surgical are used for knee osteoarthritis. Hyaluronic acid injection is a nonsurgical popular treatment used worldwide. The aim of this study was to demonstrate the effect of hyaluronic acid injections on postural stability in individuals with bilateral knee osteoarthritis. Fifty patients aged between 50 and 70 years with mild and moderate bilateral knee osteoarthritis participated in our study. They were categorized into treatment (n=25) and control (n=25) groups. The treatment group received five weekly hyaluronic acid injections for both knees, whereas the control group did not receive any treatment. Postural stability and fall risk were assessed using the Biodex Stability System and clinical “Timed Up and Go” test. All the participants completed the study. The treatment group showed significant decrease in postural stability and fall risk scores after five hyaluronic acid injections. In contrast, the control group showed significant increase. This study illustrated that five intra-articular hyaluronic acid injections could significantly improve postural stability and fall risk in bilateral knee osteoarthritis patients. This trial is registered with: NCT02063373.